(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this research is to analyze the representation of radical feminism in early 1930sHindi plays, a time period before the phrase was ever introduced to literature. Dhruvsvamini, written byIndian author Jaishankar Prasad, is an attempt to promote Radical Feminism to traditionalists in India. Bywriting this play, he sparked a sober debate on controversial topics including domestic tyranny, polygamy,sexuality, the freedom to divorce, and remarriage. Although the term Radical Feminism did not appear inwestern literature until the 1960s, this study argues that the germ of these ideas may be seen in Prasad’splays from the early 20th century. This study highlights his debt to Buddhism and the ideas ofcontemporary Indian feminist activists. The drama Dhruvsvamini has been analyzed by doing a literaturestudy. The final product of this research would be an analysis of radical feminism as it appears in Hinditheater.